Stitching My Health: Ergonomics of an Emotional Design Idea for Elderly Well-Being - Seker, Melek Seyma; Cimen, Adviye Ayca Unluer (SPRINGER INTERNATIONAL PUBLISHING AG, 2025)
Purpose This project was conducted with the purpose of putting forth a design that serves elderly well-being from a not commonly touched upon perspective while using emotional design by Norman and Heuristics by Nielsen. Methodology Following design thinking principles, a comprehensive literature review, a benchmark analysis was made. After creating personas, sketch designs were made and analysis through sketched scenarios on the context of emotional design principles and heuristics were conducted. Design Process: From the information deducted from the literature review and benchmark analysis, a user group was formed. A design was made in contribution to the mental and physical health of the users. The usability of the design was discussed through scenarios and a redesign was made using a different approach on the social engagement issue. Redesign was also discussed through scenarios and looked promising. Discussion and Future Works: In this project we created an experience of turning a problem into a happy feeling through a design created with the Emotional Design principles. In the future work, this design can be upgraded into a health tracking system. In addition, social engagement part of the design can be more elaborated, and an experience of sharing problems among users of the same design can be created.
Keywords: emotional design; heuristics; elderly health; elderly well-being; design process; design thinking; medication; mental health; Computer Science; Telecommunications